Effect of gut microbiome modulation on muscle function and cognition: the PROMOTe randomised controlled trial - Mary Ni Lochlainn; Ruth C. E. Bowyer; Janne Marie Moll; María Paz García; Samuel Wadge; Andrei-Florin Baleanu; Ayrun Nessa; Alyce Sheedy; Gulsah Akdag; Deborah Hart; Giulia Raffaele; Paul T. Seed; et al. (Nature Communications)
Abstract Studies suggest that inducing gut microbiota changes may alter both muscle physiology and cognitive behaviour. Gut microbiota may play a role in both anabolic resistance of older muscle, and cognition. In this placebo controlled double blinded randomised controlled trial of 36 twin pairs (72 individuals), aged ≥60, each twin pair are block randomised to receive either placebo or prebiotic daily for 12 weeks. Resistance exercise and branched chain amino acid (BCAA) supplementation is prescribed to all participants. Outcomes are physical function and cognition. The trial is carried out remotely using video visits, online questionnaires and cognitive testing, and posting of equipment and biological samples. The prebiotic supplement is well tolerated and results in a changed gut microbiome [e.g., increased relative Bifidobacterium abundance]. There is no significant difference between prebiotic and placebo for the primary outcome of chair rise time (β = 0.579; 95% CI −1.080-2.239 p = 0.494). The prebiotic improves cognition (factor score versus placebo (β = −0.482; 95% CI,−0.813, −0.141; p = 0.014)). Our results demonstrate that cheap and readily available gut microbiome interventions may improve cognition in our ageing population. We illustrate the feasibility of remotely delivered trials for older people, which could reduce under-representation of older people in clinical trials. ClinicalTrials.gov registration: NCT04309292.